2020
DOI: 10.1051/e3sconf/202015101031
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Cortisol and Progesterone Concentrations in Post Partus of Etawah Crossbreed Goat

Abstract: Progesterone (P4) is a dominant hormone during pregnancy. In the later stage of pregnancy, the stress hormone particularly cortisol (C) may increase for initiating the parturition process as a consequence of fetal stress. This study was a preliminary study to compare the concentration of P4 and C in feces of Etawah Crossbreed Goat during their last stage of pregnancy and post partus. This study used 5 pregnant Etawah Crossbreed Goats (t 20th weeks) of pregnancy. Fecal samples were collected in the 20th week of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…In Ruminant species such as Larter et al, (1994), Kornmatisuk et al, (2007, Isobe et al, (2005) in cows, Hattab et al, (2000), Arunji, (2008), Ashok, (2011 in buffaloes and Jack et al, (2012) in goats. Extraction of fecal progesterone using 90% methanol in black rhinoceros by Edwards et al, (2014), Chelonians by Umapathy et al, (2015) and by 80% methanol in cattle by Palme et al, (1997), goats by Airin et al, (2020), ewes by Amaral et al, (2019), Tsushima leopard cat by Adachi et al, (2010) as well as in Asian Elephants by Kumar et al, (2014Kumar et al, ( , 2019 and guanacos by Marozzi et al, (2019). This study showed a high FPM (5α-pregnan-3α-ol-20-one) value using 90% methanol as a solvent in the dried fecal sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ruminant species such as Larter et al, (1994), Kornmatisuk et al, (2007, Isobe et al, (2005) in cows, Hattab et al, (2000), Arunji, (2008), Ashok, (2011 in buffaloes and Jack et al, (2012) in goats. Extraction of fecal progesterone using 90% methanol in black rhinoceros by Edwards et al, (2014), Chelonians by Umapathy et al, (2015) and by 80% methanol in cattle by Palme et al, (1997), goats by Airin et al, (2020), ewes by Amaral et al, (2019), Tsushima leopard cat by Adachi et al, (2010) as well as in Asian Elephants by Kumar et al, (2014Kumar et al, ( , 2019 and guanacos by Marozzi et al, (2019). This study showed a high FPM (5α-pregnan-3α-ol-20-one) value using 90% methanol as a solvent in the dried fecal sample.…”
Section: Resultsmentioning
confidence: 99%
“…Methanol was used for extraction of fecal steroids in Felid (Graham et al, 1995), Exotic cat (Putranto et al, 2006), White rhinoceros (Schwarzenberger and Walzer, 1995), Black rhinoceros (Schwarzenberger et al, 1993a), Cattle (Schwarzenberger et a. 1996a(Schwarzenberger et a. , 1996b(Schwarzenberger et a. , 1996cIsobe et al, 2005), Ruminant (Kornmatitsuk et al, 2007;Larter et al, 1994), Buffalo (Hattab et al, 2000;Palme et al, 1997;Arunji, 2008;Ashok, 2011), Bengal tiger (Putranto et al, 2006), Goat (Airin et al, 2020). The fecal samples were extracted with diethyl ether in Cattle (Mostl et al, 1984;Hirata and Mori, 1995), Caribou (Desaulnier et al, 1989;Messier et al, 1990), Sow (Choi et al, 1987), Giant ant-eater (Mostl et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Glucocorticoid hormones (GC) in circulation and feces can indicate a response to psychological and nutritional stress. According to Airin et al (2020), when the body experiences stress and an increase in cortisol hormone, it can affect the levels of thyroid hormones, particularly T4. Inadequate energy intake caused by stress can also impact the process of gluconeogenesis, which increases by converting T4 into T3 to aid the body's metabolic process.…”
Section: Introductionmentioning
confidence: 99%
“…However, invasive sample collection can induce stress on the animal during handling and restraint resulting in a bias in the analysis (Sheriff et al, 2011;Rain et al, 2022). Recently non-invasive techniques for monitoring hormone levels using fecal samples have become a preferred tool for field researchers (Airin et al, 2020(Airin et al, , 2022Laura et al, 2020;Yuniarti et al, 2022;Arif et al, 2024). The excretion rate of metabolites is correlated to hormone levels in circulation.…”
Section: Introductionmentioning
confidence: 99%